TARI INDANG PADUSI DI KAMPUNG BUDAYA NAGARI JAWI JAWI KABUPATEN SOLOK SUMATERA BARAT: DALAM PERSPEKTIF ETIKA DAN ESTETIKA - Yudhitia Wardi; Erlinda Erlinda; Yarlis Yarlis (Garak Jo Garik : Jurnal Pengkajian dan Penciptaan Seni, 2023)
This research title is Female Indang dance in cultural village Nagari Jawi Jawi, Solok Regency, West Sumatra from an ethical and aesthetic perspective. The purpose of this research is to find out about Female Indang dance from an ethical and aesthetic point of view. In this research writing, the writer used a qualitative method that is a description of the analysis, which means all data obtained, both written data and data in the field, are described and then analyzed according to the research problem. The theory that the writer used in this research is the ethical theory proposed by K. Bertens, he stated that ethics can be divided into descriptive ethics and normative ethics and, an aesthetic theory proposed by Dharsono Sony Kartika, he stated that there are five conditions of beauty, namely: unity, harmony, symmetry, balance, and conflict (contras).The beauty of this dance can be seen by its shape and by the value contained in the female Indang dance. Judging from the skill of movement, makeup, and costumes, Dendang (verse) has its own beauty of form and value. Female Indang dance is a dance work sourced from male Indang dance. The presence of female Indang dance experienced pros and cons, especially from Ninik Mamak circles who thought it was unethical for a Baselo woman to dance in public. Along with the times and if women still maintain the provisions, maybe female dancers today can be tolerated.